Clinical significance and biological functions of chemokine CXCL3 in head and neck squamous cell carcinoma. Issue 12 (22nd December 2021) - Guan, Jian; Weng, Jinru; Ren, Qiaosheng; Zhang, Chunbin; Hu, Liantao; Deng, Wenjun; Lu, Shizhen; Dong, Xinyu; Li, Weidong; Li, Yue; Wang, Weiqun
Abstract: CXCL3 plays extensive roles in tumorigenesis in various types of human cancers through its roles in tumor cell differentiation, invasion, and migration. However, the mechanisms of CXCL3 in head and neck squamous cell carcinoma (HNSCC) remain unclear. In our study, multiple databases were used to explore the expression level, prognostic value, and related mechanisms of CXCL3 in human HNSCC through bioinformatic methods. We also performed further experiments in vivo and in vitro to evaluate the expression of CXCL3 in a human head and neck tissue microarray and the underlying effect mechanisms of CXCL3 on the tumor biology of HNSCC tumor cells. The result showed that the expression level of CXCL3 in patients with HNSCC was significantly higher as compared with that in normal tissues ( P <0.05). Kaplan–Meier survival analysis demonstrated that patients with high CXCL3 expression had a lower overall survival rate ( P =0.038). CXCL3 was further identified as an independent prognostic factor for HNSCC patients by Cox regression analysis, and GSEA exhibited that several signaling pathways including Apoptosis, Toll-like receptor, Nod-like receptor, Jak-STAT, and MAPK signaling pathways may be involved in the tumorigenesis of HNSCC. CAL27 cells overexpressing or HNSCC cells treated with exogenous CXCL3 exhibited enhanced cell malignant behaviors, whereas down-regulating CXCL3 expression resulted in decreased malignant behaviors in HSC4 cells. In addition, CXCL3 may affect the expression of several genes, including ERK1/2, Bcl-2, Bax, STAT3, and NF-κB. In summary, our bioinformatics and experiment findings effectively suggest the information of CXCL3 expression, roles, and the potential regulatory network in HNSCC.